IMPLEMENTATION AND RESPONSE OF TEACHERS AND STUDENTS TO THE INDEPENDENT CURRICULUM AT SMA NEGERI 4 SUNGAI RAYA - Shilmy Purnama (Sean Institute, 2023)
Research was conducted to determine the implementation and response of teachers and students to the independent curriculum learning system. The migration of the 2013 curriculum to the independent curriculum required a lot of adjustments for both teachers and students. Even high school level schools which have the status of driving schools have not yet fully implemented the independent curriculum. SMA Negeri 4 Sungai Raya is a school that is adapting to implementing an independent curriculum. Teachers at SMA Negeri 4 Sungai Raya still need special activities to improve their professionalism in implementing the independent curriculum. This research uses descriptive qualitative methods. Data collection through observation, interviews and documentation. Data analysis was carried out according to Milles and Huberman, data presentation was divided based on problem boundaries. The results of the research show that SMA 4 Sungai Raya has not implemented an independent curriculum at all grade levels. The implementation of learning based on the independent curriculum is only for grades 10 and 11. In its implementation, this driving school focuses on increasing the talents, interests and competencies of its students as well as overcoming learning loss due to the Covid-19 pandemic. Apart from that, developing soft skills and traits in accordance with the Pancasila learning profile. SMA Negeri 4 Sungai Raya only has 2 teachers who have the authority to manage and direct the implementation system to the assessment and reporting of student grades in the independent curriculum. These 2 teachers are also teachers who have busy teaching schedules. So the two teachers need a companion. The accompanying teacher chosen is a Guidance Counseling teacher. The role of the two teachers and the Guidance Counseling teacher in the independent curriculum implementation system is to provide input to students regarding student decisions with parental approval.